0
$\begingroup$

How do I calculate:

$$\lim \limits_{n \to \infty}\left(1-e^{\left(\frac{t+ \log^2(n)}{t-\log(n)}\right)}\right)^n$$

It's from a Statistics exercise, I haven't done analysis for a long time. I think what I have to do is try to get it to look something like

$$\lim \limits_{n \to \infty}\left(1+\frac{A}{n}\right)^n$$ for a suitable $A$ and apply the standard limit $$\lim \limits_{n \to \infty}\left(1+\frac{A}{n}\right)^n = e^A$$ I am stuck though.

$\endgroup$
1
$\begingroup$

First note that as $n\to\infty$ we have \begin{align} \frac{t+ \log^2(n)}{t-\log(n)} &\sim-\log(n)\\ &\to-\infty \end{align} hence $e^{\frac{t+\log^2(n)}{t-\log(n)}}\to 0$. Since $\log(1+\varepsilon)\sim\varepsilon$ as $\varepsilon\to 0$, by taking logarithm, we have \begin{align} \lim_{n\to\infty}\log\left(1-e^{\frac{t+\log^2(n)}{t-\log(n)}}\right)^n &=\lim_{n \to \infty}n\log\left(1-e^{\frac{t+\log^2(n)}{t-\log(n)}}\right)\\ &\sim -ne^{\frac{t+\log^2(n)}{t-\log(n)}} \end{align} By taking logarithm again: \begin{align} \lim_{n\to\infty}\log\left(ne^{\frac{t+\log^2(n)}{t-\log(n)}}\right) &=\log n+\frac{t+\log^2(n)}{t-\log(n)}\\ &=\frac{1+\log(n)}{t-\log(n)}t\\ &\to -t \end{align} Consequently, $$\lim_{n\to\infty}\left(1-e^{\frac{t+\log^2(n)}{t-\log(n)}}\right)^n=e^{-e^{-t}}$$

$\endgroup$
  • $\begingroup$ I am so terribly sorry but I made a typo. $\endgroup$ – Noppawee Apichonpongpan Aug 6 '18 at 15:02
  • $\begingroup$ Answer updated. $\endgroup$ – Fabio Lucchini Aug 6 '18 at 16:35

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.